Long‐term outcome of vein of Galen malformation. (12th November 2019) - Taffin, Hélène; Maurey, Hélène; Ozanne, Augustin; Durand, Philippe; Husson, Béatrice; Knebel, Jean‐François; Adamsbaum, Catherine; Deiva, Kumaran; Saliou, Guillaume
Abstract : Aim: To describe the long‐term outcomes of children by the time they reached school age with vein of Galen aneurysmal malformation (VGAM). Method: This was a retrospective observational study on a consecutive cohort of patients with VGAM. We included patients with at least one Francophone parent, aged between 6 and 11 years at the time of long‐term evaluation. The neurological outcome was assessed with the King's Outcome Scale for Childhood Injury score and eight neurological and behavioural items from the Rivermead Postconcussion Symptoms questionnaire. Results: All 52 patients (17 females, 32 males [data missing for n =3]) with at least one Francophone parent (5 fetuses and 47 children) were included. At the long‐term evaluation time‐point, 33 patients were alive and 19 patients had died. Risk of postnatal death was associated with severe neonatal cardiac failure ( p =0.007) or isosystemic or suprasystemic pulmonary hypertension ( p =0.014). Among survivors, 19 had a good outcome with normal schooling and 14 had a poor outcome. Moreover, among the good outcome patients, a large proportion had neurodevelopmental alterations. Interpretation: Long‐term outcome of patients with VGAM appears to be less favourable than outcome described at the short‐ and medium‐term, even in the absence of encephalomalacia at birth. Even patients with good outcome often have neuropsychological disorders that may have repercussions on learning and requiring appropriate rehabilitation or medical management. What this paper adds: Long‐term outcome appears to be less favourable than described at short‐ and medium‐term follow‐up. Even patients with good outcome at these time‐points often have minor neuropsychological disorders. What this paper adds: Long‐term outcome appears to be less favourable than described at short‐ and medium‐term follow‐up. Even patients with good outcome at these time‐points often have minor neuropsychological disorders. This article is commented on by Ganesan on page 666 of this issue.